Dickens and the American Millennium: The Uniformitarian Argument of Martin Chuzzlewit - Nancy Aycock Metz (Cahiers Victoriens et Edouardiens)
This essay builds on recent critical discussion of Dickens’s novels in terms of the ‘uniformitarian’ and ‘catastrophist’ paradigms of time and change, then current in contemporary geological discourse. While previous scholarship has mainly focused on these ideas as they are represented in Dickens’s later novels, this essay examines an earlier text, Martin Chuzzlewit, the only Dickens novel to reference Lyell’s Elements of Geology by name and, (through its American subplot), the only novel to explore fundamentally contrasting paradigms of origins, history, and nationhood. The providential plot of Martin Chuzzlewit, its deus ex machina conclusion, and continent-spanning coincidences would seem to describe a ‘catastrophist’ narrative structure, one characterized by interventions that interrupt the status quo and suddenly alter history. But Dickens also shows how catastrophic events are often contained within a more expansive uniformitarian time frame. He depicts human beings as small and vulnerable against ancient earthscapes of ocean, plain, forest, and wilderness, and exposes as myopic the narcissism of the vaunting, needy ego, with its self-centered construction of the world. Dickens makes these ideas part of a nationalist argument in deconstructing the American historical narrative. Americans found the closest analogue for their democratic experiment in the favourite example of the catastrophists—the Biblical deluge. Like the flood, the American Revolution had supposedly washed away the sins and traces of the past, permitting a momentous new start. But Dickens proposed a counter-narrative of the ‘New’ World evoking its still-visible primeval landscape and its disappearing ‘savage’ races. Against the American view of democracy as a recent, decisive intervention in human history permanently altering its trajectory, Dickens urged the unknowability of origins, the fragility of the human race and the certainty of change.